Potential Germination Success of Exotic and Native Trees Coexisting in Central Spain Riparian Forests. (10th April 2016) - Cabra-Rivas, Isabel; Castro-Díez, Pilar
Abstract : We compared potential germination success (i.e., percentage of produced seeds that germinate under optimal conditions), the percentage of empty and insect-damaged seeds, germinability (G m a x ), and time to germination (T g e r m ) between the exotics Ailanthus altissima, Robinia pseudoacacia, and Ulmus pumila and two coexisting native trees ( Fraxinus angustifolia and Ulmus minor ) in the riparian forests of Central Spain. Additionally, we tested the effect of seed age, seed bank type (canopy or soil) and population onG m a x andT g e r m of A. altissima and R. pseudoacacia, which are seed-banking species. Species ranked by their potential germination success were A. altissima > U. pumila > R. pseudoacacia > U. minor > F. angustifolia . The combination of a highG m a x and negligible seed insect-damage provided A. altissima with a potential germination advantage over the natives, which were the least successful due to an extremely high percentage of empty seeds or a very lowG m a x . R. pseudoacacia showed high vulnerability to insect seed predation which might be compensated with the maintenance of persistent seed banks with highG m a x .G m a x andT g e r m were strongly affected by seed age in the seed-banking invaders, but between-seed bank variation ofG m a x andT g e r m did not show a consistent pattern across species and populations.